Cost-effectiveness of adherence-enhancing interventions: a systematic review. (2nd January 2016) - Simon-Tuval, Tzahit; Neumann, Peter J.; Greenberg, Dan
Abstract: Low patient adherence to health-related interventions is a major barrier to achieving healthcare goals and is associated with very high avoidable costs. Although several studies suggest that adherence-enhancing interventions can improve health outcomes, economic evaluations of these interventions are scarce. Systematic reviews published to date are limited to interventions to enhance adherence to pharmaceuticals or to specific diseases and interventions. The authors' objective was to examine the evidence regarding the cost-effectiveness of adherence-enhancing interventions in healthcare and what conclusion could be drawn about these interventions. The present systematic review included 43 original studies and assessed the current evidence regarding the cost-effectiveness of a broad array of interventions aimed at enhancing adherence to medications, medical devices, screening tests and lifestyle behaviors. The authors found that although the majority of adherence-enhancing interventions were cost-effective or cost-saving, variation exists within different intervention types. Further research on the sustainability of adherence improvements is needed in order to accurately evaluate interventions' long-term benefits.